'Adipaging': ageing and obesity share biological hallmarks related to a dysfunctional adipose tissue. (10th May 2016) - Pérez, Laura M.; Pareja‐Galeano, Helios; Sanchis‐Gomar, Fabián; Emanuele, Enzo; Lucia, Alejandro; Gálvez, Beatriz G.
Abstract : Schematic representation of the interplay between a pathological state, obesity, and a physiological process, ageing: a new concept, 'adipaging', postulates a common soil for the two conditions. Abstract: The increasing ageing of our societies is accompanied by a pandemic of obesity and related cardiometabolic disorders. Progressive dysfunction of the white adipose tissue is increasingly recognized as an important hallmark of the ageing process, which in turn contributes to metabolic alterations, multi‐organ damage and a systemic pro‐inflammatory state ('inflammageing'). On the other hand, obesity, the paradigm of adipose tissue dysfunction, shares numerous biological similarities with the normal ageing process such as chronic inflammation and multi‐system alterations. Accordingly, understanding the interplay between accelerated ageing related to obesity and adipose tissue dysfunction is critical to gain insight into the ageing process in general as well as into the pathophysiology of obesity and other related conditions. Here we postulate the concept of 'adipaging' to illustrate the common links between ageing and obesity and the fact that, to a great extent, obese adults are prematurely aged individuals.